Solution:
The equation of a line that passes through a point is expressed as
![\begin{gathered} y-y_1=m(x-x_1)\text{ ---- equation 1} \\ where \\ m\Rightarrow slope\text{ of the line} \\ y\Rightarrow y-intercept\text{ of the line} \\ (x_1,y_1)\Rightarrow coordinate\text{ of the point through which the line passes} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/wrvyx7bjshih1jek27chl7oss19op1a9xu.png)
Two lines A and B are said to be perpendicular if the slope of line A is equal to the negative reciprocal of the slope of line B.
Thus, lines A and B are perpendicular if
![m_A=-(1)/(m_B)\text{ ---- equation 2}](https://img.qammunity.org/2023/formulas/mathematics/high-school/1byj7cv2cbfipv0hgdgqic7lkh8vt9lllw.png)
Let the line equation
![y-4=(2)/(5)(x-6)](https://img.qammunity.org/2023/formulas/mathematics/high-school/yfrb7iwukne4cknr3jteufbzt3jp7kl525.png)
represent the line A.
step 1: Evaluate the slope of line A.
Comparing the equation of line A with equation 1, we can conclude that the slope of the line A is
![m_A=(2)/(5)](https://img.qammunity.org/2023/formulas/mathematics/high-school/byzrhv6x932gxm984v0jfbwk7meqc29v55.png)
step 2: Evaluate the slope of line B.
Since lines A and B are perpendicular, we have
![\begin{gathered} From\text{ equation 2,} \\ \begin{equation*} m_A=-(1)/(m_B) \end{equation*} \\ where \\ m_A=(2)/(5) \\ thus, \\ (2)/(5)=-(1)/(m_B) \\ cross-multiply \\ -2m_B=5 \\ divide\text{ both sides by -2} \\ (-2m_B)/(-2)=(5)/(-2) \\ \Rightarrow m_B=-(5)/(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/jf8bmsefifhl18y4yonnfu1uf7ie22k44y.png)
step 3: Evaluate the line B.
Since the line B passes through the points (-3,2), recall from equation 1
![\begin{equation*} y-y_1=m(x-x_1)\text{ } \end{equation*}](https://img.qammunity.org/2023/formulas/mathematics/high-school/y830sqd1wxm42qbeke6xy5ud4hzv5hsikq.png)
where
![\begin{gathered} x_1=-3 \\ y_1=2 \\ m=m_B=-(5)/(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/cvsfr25kii4yr2m4ibf3q1fcvraeq2k9yl.png)
Substitute these values into equation 1.
Thus,
![\begin{gathered} y-2=-(5)/(2)(x-(-3)) \\ \Rightarrow y-2=-(5)/(2)(x+3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/et7jd2bzy9mn4bm2g9k15jp2p0z9f87z76.png)
Hence, the equation of the line is
![y-2=-(5)/(2)(x+3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/lv8kv6ie742xbnn2dl8do23wkkc8w40jjm.png)
The correct option is A